2021
DOI: 10.3389/fpls.2021.656783
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Bird and Insect Flower Traits in Fritillaria L. (Liliaceae)

Abstract: Pollinators are often perceived as a primary selective agent influencing flower traits such as colour, size, and nectar properties. The genus Fritillaria L. (Liliaceae), comprising approximately 150 species, is described as generally insect pollinated. However, there are at least three exceptions: two hummingbird-pollinated North American species and one passerine-pollinated Asian species. Despite this variation in pollination, little is known about flower traits that may accompany this shift in fritillaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…For example, red flowers attract butterflies, night-scented flowers attract moths, long-spurred flowers attract longtongued flies, the lack of spur in flowers attracts bees or wasps, and deceptive flowers attract carpenter bees. More recently published studies [74,75] revealed the appearance of some new floral characters within the Fritillaria genus related to floral morphology and reward, which led to shifts of principal pollinators. For instance, newly derived red and orange flowers in F. recurve, F. gentneri, and F. imperialis, as well as the alteration in their sugar and amino-acid content in nectar, have led to a pollinator shift for these species from insects to birds.…”
Section: Floral Adaptions To Particular Groups Of Pollinators: Pollin...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, red flowers attract butterflies, night-scented flowers attract moths, long-spurred flowers attract longtongued flies, the lack of spur in flowers attracts bees or wasps, and deceptive flowers attract carpenter bees. More recently published studies [74,75] revealed the appearance of some new floral characters within the Fritillaria genus related to floral morphology and reward, which led to shifts of principal pollinators. For instance, newly derived red and orange flowers in F. recurve, F. gentneri, and F. imperialis, as well as the alteration in their sugar and amino-acid content in nectar, have led to a pollinator shift for these species from insects to birds.…”
Section: Floral Adaptions To Particular Groups Of Pollinators: Pollin...mentioning
confidence: 99%
“…Examples of such adaptations to a new particular group of pollinators in far-related taxa have also been observed in Fritillaria genus, where species pollinated mainly by insects include twice-evolved ornithophily syndrome for F. recurve, F. gentneri from the Liliorhiza subgenus (pollinated by hummingbirds), and F. imperialis from the Petilium subgenus (pollinated by passerine birds). Interestingly, reversal shifts of a pollinator from ornithophily to myophily were also present [75]. Another excellent example of the diversification of pollination strategies within a single genus is presented by Disa genus, in which a monophyletic group of 27 studied taxa revealed multiple independent radial evolutions of various pollination syndromes [73].…”
Section: Evolution Of Floral Characters: Synapomorphies Vs Homoplasiesmentioning
confidence: 99%
“…Remarkably, generalist passerines have been demonstrated as the most effective pollinators for winter flowering plants in regions where sunbirds are absent, especially in dry seasons and in the islands (Chen et al, 2019). These include species such as Fritillaria imperialis (Roguz et al, 2021), Firmiana spp. (Huang et al, 2018), Rhodoleia spp.…”
Section: Introductionmentioning
confidence: 99%